PROFIL BERPIKIR KREATIF SISWA SD DALAM MENYELESAIKAN MASALAH PERSEGI MENGGUNAKAN TANGRAM BERDASARKAN LEVEL BERPIKIR VAN HIELE - Erfan Yudianto; Titik Sugiarti; Sofi Astri; Feny Rita Fiantika (Universitas Ahmad Dahlan, 2021)
Creative thinking capability is a capability to deliver a new idea by varied means in solving problem. This research aims to describe creative thinking capability in solving square and rectangle problem reviewed by van Hiele’s thinking level of 4th grade students of SDN Kejayan 1 Bondowoso. This research type is descriptive research with qualitative approach. Data collecting method using test and interview. The used test is van Hiele’s geometry thinking test and creative thinking capability test related to square and rectangle. Research output shows that student at pre-visualization phase has less creative and sufficient creative thinking capability. Student at visualization phase, has sufficient creative and less creative thinking capability. Student at analysis level has sufficient creative thinking capability.